Niat Membeli dan Kepercayaan Pelanggan Online Marketplace - Sitorus, Marthaleina Ruminda; Anggiani, Sarfilianty; Yuliantini, Yuliantini; Keke, Yulianti; Ghafar, Abdul (Institut Transportasi dan Logistik Trisakti, 2022)
This research is to determine the factors that influence the purchase intention of customers or potential customers that mediated by trust in online marketplaces during the COVID-19 pandemic and entering the digital era 4.0. This study used quantitative descriptive method by distributing questionnaires to respondents. The sample used was 306 respondents. This research uses path analysis techniques with the Structural Equation Model (SEM) Partial Least Square (PLS) method with the help of SmartPLS software. The results of the direct influence hypothesis test show a significant and positive influence on each latent variable except for the results of the hypothesis test of the effect of ease on trust which has a direct but not significant and positive influence. While in the indirect influence test, latent variables have a significant and positive indirect influence, except for the indirect influence of convenience on purchase intention mediated by customer or prospective customer confidence. Thus, marketplace application business people are expected to improve digital marketing services, especially in the ease of using applications so that they can increase purchase intent that further makes transactions on marketplace applications.